Prove the Following Trigonometric Identities. `Sqrt((1 + Sin A)/(1 - Sin A)) = Sec a + Tan a - Mathematics

Advertisements
Advertisements

Prove the following trigonometric identities.

`sqrt((1 + sin A)/(1 - sin A)) = sec A + tan A`

Advertisements

Solution

We need to prove `sqrt((1 + sin A)/(1 - sin A)) = sec A + tan A`

Here, rationalising the L.H.S, we get

`sqrt((1 + sin A)/(1 - sin A)) = sqrt((1+ sin A)/(1 - sin A)) xx sqrt((1 + sin A)/(1 + sin A))`

`= sqrt((1 + sin A)^2/(1 - sin^2 A)`

Further using the property, `sin^2 theta + cos^2 theta = 1` we get

So,

`sqrt((1 - cos A)/(1 - cos^2 A)) = sqrt((1 -  cos A)^2/sin^2 A)`

`= (1 - cos A)/sin A`

`= 1/sin A - cos A/sin A`

`=cosec A  - cot A`

Hence proved.

  Is there an error in this question or solution?
Chapter 11: Trigonometric Identities - Exercise 11.1 [Page 44]

APPEARS IN

RD Sharma Class 10 Maths
Chapter 11 Trigonometric Identities
Exercise 11.1 | Q 37 | Page 44

RELATED QUESTIONS

 

If `sec alpha=2/sqrt3`  , then find the value of `(1-cosecalpha)/(1+cosecalpha)` where α is in IV quadrant.

 

Prove that:

sec2θ + cosec2θ = sec2θ x cosec2θ


Prove the following identities:

`(i) (sinθ + cosecθ)^2 + (cosθ + secθ)^2 = 7 + tan^2 θ + cot^2 θ`

`(ii) (sinθ + secθ)^2 + (cosθ + cosecθ)^2 = (1 + secθ cosecθ)^2`

`(iii) sec^4 θ– sec^2 θ = tan^4 θ + tan^2 θ`


(1 + tan θ + sec θ) (1 + cot θ − cosec θ) = ______.


Prove the following identities, where the angles involved are acute angles for which the expressions are defined:

`(tan theta)/(1-cot theta) + (cot theta)/(1-tan theta) = 1+secthetacosectheta`

[Hint: Write the expression in terms of sinθ and cosθ]


if `cos theta = 5/13` where `theta` is an acute angle. Find the value of `sin theta`


Prove the following trigonometric identities.

`(cos^2 theta)/sin theta - cosec theta +  sin theta  = 0`


Prove the following trigonometric identities.

`((1 + tan^2 theta)cot theta)/(cosec^2 theta)   = tan theta`


Prove the following trigonometric identities.

sin2 A cos2 B − cos2 A sin2 B = sin2 A − sin2 B


if `cosec theta - sin theta = a^3`, `sec theta - cos theta = b^3` prove that `a^2 b^2 (a^2 + b^2) = 1`


Prove.
cosecA - cosec2 A = cot4 A + cot2 A


Prove the following identitie:

(1 + tanA + secA)(1 + cotA - cosecA) = 2


`(1 + cot^2 theta ) sin^2 theta =1`


`tan theta/(1+ tan^2 theta)^2 + cottheta/(1+ cot^2 theta)^2 = sin theta cos theta`


`(sin theta +cos theta )/(sin theta - cos theta)+(sin theta- cos theta)/(sin theta + cos theta) = 2/((sin^2 theta - cos ^2 theta)) = 2/((2 sin^2 theta -1))`


Show that none of the following is an identity: 

`sin^2 theta + sin  theta =2`


Prove that `( sintheta - 2 sin ^3 theta ) = ( 2 cos ^3 theta - cos theta) tan theta`


If `( cosec theta + cot theta ) =m and ( cosec theta - cot theta ) = n, ` show that mn = 1.


If `cos theta = 7/25 , "write the value of" ( tan theta + cot theta).`


Eliminate θ, if
x = 3 cosec θ + 4 cot θ
y = 4 cosec θ – 3 cot θ


Prove that:

`"tan A"/(1 + "tan"^2 "A")^2 + "Cot A"/(1 + "Cot"^2 "A")^2 = "sin A cos A"`.


If `secθ = 25/7 ` then find tanθ.


\[\frac{\tan \theta}{\sec \theta - 1} + \frac{\tan \theta}{\sec \theta + 1}\] is equal to 


Prove the following identity :

`sinθ(1 + tanθ) + cosθ(1 +cotθ) = secθ + cosecθ` 


Prove the following identity :

`tan^2A - sin^2A = tan^2A.sin^2A`


Prove the following identity :

(secA - cosA)(secA + cosA) = `sin^2A + tan^2A`


Prove the following identity :

`(1 + cosA)/(1 - cosA) = (cosecA + cotA)^2`


Prove that :(sinθ+cosecθ)2+(cosθ+ secθ)2 = 7 + tan2 θ+cotθ.


Prove that tan2Φ + cot2Φ + 2 = sec2Φ.cosec2Φ.


Prove that sin4θ - cos4θ = sin2θ - cos2θ
= 2sin2θ - 1
= 1 - 2 cos2θ


Prove that `((tan 20°)/(cosec 70°))^2 + ((cot 20°)/(sec 70°))^2  = 1`


Prove that: `1/(cosec A - cot A) - 1/sin A = 1/sin A - 1/(cosec A + cot A)`


Prove the following identities.

`sqrt((1 + sin theta)/(1 - sin theta)` = sec θ + tan θ


Prove the following identities.

(sin θ + sec θ)2 + (cos θ + cosec θ)2 = 1 + (sec θ + cosec θ)2


Prove the following identities.

sec4 θ (1 – sin4 θ) – 2 tan2 θ = 1


Prove the following identities.

`(cot theta - cos theta)/(cot theta + cos theta) = ("cosec"  theta - 1)/("cosec"  theta + 1)`


Prove the following identities.

`(sin "A" - sin "B")/(cos "A" + cos "B") + (cos "A" - cos "B")/(sin "A" + sin "B")`


If sin θ + cos θ = `sqrt(3)`, then prove that tan θ + cot θ = 1


If `sqrt(3)` sin θ – cos θ = θ, then show that tan 3θ = `(3tan theta - tan^3 theta)/(1 - 3 tan^2 theta)`


If cot θ + tan θ = x and sec θ – cos θ = y, then prove that `(x^2y)^(2/3) – (xy^2)^(2/3)` = 1


If a cos θ – b sin θ = c, then prove that (a sin θ + b cos θ) = `±  sqrt("a"^2 + "b"^2 -"c"^2)`


Choose the correct alternative:

1 + cot2θ = ? 


Choose the correct alternative:

`(1 + cot^2"A")/(1 + tan^2"A")` = ?


If sec θ + tan θ = `sqrt(3)`, complete the activity to find the value of sec θ – tan θ

Activity:

`square` = 1 + tan2θ    ......[Fundamental trigonometric identity]

`square` – tan2θ = 1

(sec θ + tan θ) . (sec θ – tan θ) = `square`

`sqrt(3)*(sectheta - tan theta)` = 1

(sec θ – tan θ) = `square`


Prove that `(sin^2theta)/(cos theta) + cos theta` = sec θ


If tan θ + cot θ = 2, then tan2θ + cot2θ = ?


Prove that sec2θ − cos2θ = tan2θ + sin2θ


Prove that `(cos^2theta)/(sintheta) + sintheta` = cosec θ


If sec θ = `41/40`, then find values of sin θ, cot θ, cosec θ


Prove that `(tan(90 - theta) + cot(90 - theta))/("cosec"  theta)` = sec θ


Prove that `(1 + sintheta)/(1 - sin theta)` = (sec θ + tan θ)2 


Prove that `"cot A"/(1 - cot"A") + "tan A"/(1 - tan "A")` = – 1


Prove that

`(cot "A" + "cosec  A" - 1)/(cot"A" - "cosec  A" + 1) = (1 + cos "A")/"sin A"`


If cos A = `(2sqrt("m"))/("m" + 1)`, then prove that cosec A = `("m" + 1)/("m" - 1)`


Prove the following:

`tanA/(1 + sec A) - tanA/(1 - sec A)` = 2cosec A


Prove the following:

`1 + (cot^2 alpha)/(1 + "cosec"  alpha)` = cosec α


Prove the following:

(sin α + cos α)(tan α + cot α) = sec α + cosec α


Complete the following activity to prove:

cotθ + tanθ = cosecθ × secθ

Activity: L.H.S. = cotθ + tanθ

= `cosθ/sinθ + square/cosθ`

= `(square + sin^2theta)/(sinθ xx cosθ)`

= `1/(sinθ xx  cosθ)` ....... ∵ `square`

= `1/sinθ xx 1/cosθ`

= `square xx secθ`

∴ L.H.S. = R.H.S.


Let x1, x2, x3 be the solutions of `tan^-1((2x + 1)/(x + 1)) + tan^-1((2x - 1)/(x - 1))` = 2tan–1(x + 1) where x1 < x2 < x3 then 2x1 + x2 + x32 is equal to ______.


If 2 cos θ + sin θ = `1(θ ≠ π/2)`, then 7 cos θ + 6 sin θ is equal to ______.


Let α, β be such that π < α – β < 3π. If sin α + sin β = `-21/65` and cos α + cos β = `-27/65`, then the value of `cos  (α - β)/2` is ______.


Share
Notifications



      Forgot password?
Use app×